2012
DOI: 10.1242/jeb.060822
|View full text |Cite
|
Sign up to set email alerts
|

Worker division of labor and endocrine physiology are associated in the harvester ant,Pogonomyrmex californicus

Abstract: SUMMARYIn Pogonomyrmex californicus harvester ants, an age-associated division of labor occurs in the worker caste, in which young workers perform in-nest tasks and older workers forage for food. Here, we tested whether this behavioral division is age based or age flexible, and whether it coincides with differential expression of systemic hormones with known roles in behavioral regulation. Whole-body content of juvenile hormone (JH) and ecdysteroids was determined in workers from (1) age-typical colonies, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 54 publications
(63 reference statements)
4
49
0
Order By: Relevance
“…Although our results confirmed that the link between age and task is flexible in ants (e.g. Sendova-Franks and Franks, 1993;Blanchard et al, 2000;Dolezal et al, 2012;Bernadou et al, 2015), not unexpectedly there was a slight increase in mortality rate with chronological age, with foragers that reverted to inner-nest workers dying somewhat sooner than 'true' inner-nest workers. This difference could be due to the fact that fat reserves were lower in foragers that reverted to inner-nest workers than in inner-nest workers that remained inner-nest workers.…”
Section: Discussionsupporting
confidence: 68%
“…Although our results confirmed that the link between age and task is flexible in ants (e.g. Sendova-Franks and Franks, 1993;Blanchard et al, 2000;Dolezal et al, 2012;Bernadou et al, 2015), not unexpectedly there was a slight increase in mortality rate with chronological age, with foragers that reverted to inner-nest workers dying somewhat sooner than 'true' inner-nest workers. This difference could be due to the fact that fat reserves were lower in foragers that reverted to inner-nest workers than in inner-nest workers that remained inner-nest workers.…”
Section: Discussionsupporting
confidence: 68%
“…A long history of research has focused on a connection between increased JH levels and foraging in social insects (Dolezal et al, 2012;Hartfelder, 2000), and we previously confirmed this pattern in H. saltator (Penick et al, 2011). Alternatively, work on biogenic amines in honey bees has found that octopamine may regulate foraging in tandem with JH, and the response to octopamine treatment is more rapid than the response to JH treatment (Schulz et al, 2002).…”
Section: Worker Division Of Laborsupporting
confidence: 63%
“…Furthermore, JH has many other functions in social insects, including behavioral modulation, longevity, fecundity and immunity (Flatt et al, 2005; Jindra et al, 2013; Dolezal et al, 2012; Wang et al, 2012); the relevance of trophallaxis-mediated JH exchange between adults remains to be explored. Considering that most, if not all, individuals in a colony must share food through trophallaxis, it will also be of interest to understand if and how individual-, or caste-specific TF-based information signals emerge.…”
Section: Discussionmentioning
confidence: 99%